Matrix‐Rigidity Cooperates With Biochemical Cues in M2 Macrophage Activation Through Increased Nuclear Deformation and Chromatin Accessibility - Seung Jae Shin; Buuvee Bayarkhangai; Khaliunsarnai Tsogtbaatar; Meng Yuxuan; Sang‐Hyun Kim; Yong‐Jae Kim; Ali Taghizadeh; Daesan Kim; Dong‐Hwee Kim; Jung‐Hwan Lee; Jeongeun Hyun; Hae‐Won Kim (Advanced Science)
Abstract Macrophages encounter a myriad of biochemical and mechanical stimuli across various tissues and pathological contexts. Notably, matrix rigidity has emerged as a pivotal regulator of macrophage activation through mechanotransduction. However, the precise mechanisms underlying the interplay between mechanical and biochemical cues within the nuclear milieu remain elusive. Here We elucidate how the increased matrix rigidity drives macrophages to amplify alternatively‐activated (M2 phenotype) signaling cooperatively with biochemical cues (e.g., IL4/13) through altered nuclear mechanics. We demonstrate that reconstructed podosome‐like F‐actins and contractility induce nucleus deformation, opening nuclear pores, which facilitates nuclear translocation of the key transcription factor STAT6. Furthermore, the altered nuclear mechanics increases chromatin accessibility induced by H3K9 methylation, particularly of M2‐associated gene promoters. These cooperative events of the mechano‐chemical signaling at the cytoskeletal‐to‐nuclear domains facilitate M2 transcriptional activation and cellular functions. We further evidence the rigidity‐primed M2 macrophages are immunosuppressive and accumulated within stiffened tumors in patients. This study proposes a mechanism by which matrix mechanics crosstalks with biochemical signals to potentiate macrophage activation through nuclear mechanosensing and chromatin modifications, offering insights into macrophage mechanobiology and its therapeutic modulations.